Dimensions of Phubbing Among Moslem Adolescents in Revolution Industry 4.0: Perspective Mental Health - Iredho Fani Reza (Fakultas Ilmu Pendidikan)
In the era industrial revolution 4.0 the impact of science and technology has a positive impact and some have a negative impact. The purpose of this research is to reveal the dimensions of phone snubbing among Muslim teenagers in the mental health perspective. This research is a type of qualitative research with a grounded theory design. Respondents in this study amounted to 97 people who were among moslem adolescents as undergraduate students at a state Islamic university in Indonesia which was determined using purposive sampling technique. The collection method uses questionnaires, interviews and observations. The main analysis method uses coding technique technique which consists of open coding, axial coding and selective coding. The results of this study conclude that the dimensions of phone snubbing among moslem adolescents include, first, ignore others and switch to gadgets, second, dependency on gadgets, third, social disconnectedness.